SCIENTOMETRIC ANALYSIS OF BIG DATA ANALYTIC AND HALAL SUPPLY CHAIN MANAGEMENT - Kuncorosidi Kuncorosidi; Daeng M. Nazier; Riznaldi Akbar; Eddy Prabowo (STIESA Press, 2024)
This study aims to conduct a scientometric analysis of